Networked Carbon Markets : Key Elements of the Mitigation Value Assessment Process - Macinante, Justin (World Bank, Washington, DC, 2016)
This paper builds on the findings of an earlier unpublished discussion paper titled ‘designing a model for networked carbon markets’, with its objective being to describe key elements of the mitigation value assessment process. The outcome of this paper will inform a model for the Networked Carbon Markets concept, to be prepared at a later date. The following section two acknowledges the subject matter of the NCM initiative, namely the diverse and heterogeneous trading schemes and other carbon pricing mechanisms that are being put in place by jurisdictions around the globe. As this is the subject of another World Bank paper, only a brief reference is included. Section three sets out a conceptual framework within which to consider the key elements described in the glossary of terms, addressed in section four and annexure ‘C’. This section also looks at different transaction scenarios, introducing the concepts of an international transaction unit and an index. Section five turns attention to the types of institutions that might be suitable to participate in the mitigation value assessment process, providing practical examples, and considering the types of expertise and tools those institutions might leverage. Section six considers options for regulatory supervision of the MV assessment process. Section seven looks in more detail at the relationship between mitigation value and the compliance value that might be attached to carbon assets and, in so doing, considers the role and function of the settlement platform. This section also considers the feasibility and potential benefits of an index. The concluding section eight looks at the next steps that might flow from this work.